PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN BANK PERKREDITAN RAKYAT â€œXâ€ KABUPATEN ROKAN HILIR-RIAU - Yapentra, Arhipen (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
The purpose of this study was to determine the effect of compensation on employee performance at Rural Bank of Rokan Hilir.. To achieve this goal, research was conducted using a sample of 31 people, using the census method (saturated sampling). The data analysis method used simple linear regression. Based on the test results on the compensation variable (X) obtained t-count is greater than t-table (3.506 > 2.045). Thus it can be concluded that the compensation variable has a positive and significant effect on the performance of employees. Rural Bank of Rokan Hilir,. The value of R. Square (R2) of 0.298 (29.8%) explains that the compensation variable contributes to the influence of the performance of employees. Rural Bank Rokan Hilir by 29.8%. While the remaining 70.2% describes other independent variables that were not observed in this study. Recommendations that can be submitted It is expected that the company will provide allowances for positions because it gets the lowest response from respondents, which is 3.15 with a category quite agree